A Review of the Antiviral Activities of Glycyrrhizic Acid, Glycyrrhetinic Acid and Glycyrrhetinic Acid Monoglucuronide - Jiawei Zuo; Tao Meng; Yuanyuan Wang; Wenjian Tang (MDPI AG, 2023)
Licorice, a natural medicine derived from the roots and rhizomes of Glycyrrhiza species, possesses a wide range of therapeutic applications, including antiviral properties. Glycyrrhizic acid (GL) and glycyrrhetinic acid (GA) are the most important active ingredients in licorice. Glycyrrhetinic acid 3-O-mono-β-d-glucuronide (GAMG) is the active metabolite of GL. GL and its metabolites have a wide range of antiviral activities against viruses, such as, the hepatitis virus, herpes virus and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and so on. Although their antiviral activity has been widely reported, the specific mechanism of action involving multiple links such as the virus itself, cells, and immunity are not clearly established. In this review, we will give an update on the role of GL and its metabolites as antiviral agents, and detail relevant evidence on the potential use and mechanisms of actions. Analyzing antivirals, their signaling, and the impacts of tissue and autoimmune protection may provide promising new therapeutic strategies.